1990
DOI: 10.21000/jasmr90010171
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Ground Water in Mine Spoil, a Renewable Resource: Star Fire Tract, Eastern Kentucky

Abstract: Toe Star Fire site is a large surface mining operation in eastern Kentucky owned and operated by Gyprus-Southem Realty. Approxlmately 10,000 acres of reclaimed, usable land will result from the ongoing mining operation by the year 201 O. Ultimately, development on the tract will depend on the avallabilityof an adequate water supply utilizing both surface and ground waters. Toe water resources of the first 1,000-acre tract of mine spoil have been investigated. Areas of groundwater recharge and discharge have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Therefore, instead of increasing stormflow because of surface compaction, the valley fills increase the baseflow portion of total streamflow. Additionally, preferential flowpaths along the spoil-bedrock interface could enhance infiltration into the VF . Unfortunately, little published research provides insight on the internal structure of valley fills and how settlement or sorting of material may affect hydrologic flowpathways. ,, Greer et al, for example, demonstrated high subsurface heterogeneity in a valley fill in Virginia using electrical resistivity imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, instead of increasing stormflow because of surface compaction, the valley fills increase the baseflow portion of total streamflow. Additionally, preferential flowpaths along the spoil-bedrock interface could enhance infiltration into the VF . Unfortunately, little published research provides insight on the internal structure of valley fills and how settlement or sorting of material may affect hydrologic flowpathways. ,, Greer et al, for example, demonstrated high subsurface heterogeneity in a valley fill in Virginia using electrical resistivity imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, preferential flowpaths along the spoil-bedrock interface could enhance infiltration into the VF . Unfortunately, little published research provides insight on the internal structure of valley fills and how settlement or sorting of material may affect hydrologic flowpathways. ,, Greer et al, for example, demonstrated high subsurface heterogeneity in a valley fill in Virginia using electrical resistivity imaging. It is reasonable to assume that the physical characteristics of the VFs affect how much water can be stored in the VFs and how the stored water is subsequently released to sustain streamflow.…”
Section: Discussionmentioning
confidence: 99%
“…Average saturated thickness of the spoil aquifer was calculated at 6.5 m; measured hydraulic conductivities ranged from 6.1 × 10 −7 to >8.8 × 10 −6 m/s. Further details of mining activities, spoil construction, and mine geology and hydrogeology of the Starfire Mine are given by (Dinger et al. , 1988, 1990; Kemp, 1990; Wunsch et al.…”
Section: Methodsmentioning
confidence: 99%
“…If PA < 5, the stratum is generally considered a non-acid producer, regardless of the neutralization potential (Sobek et al, 1978). water at the site (Wunsch et al 1992;Dinger et al 1990). Therefore, these points are "discussed only briefly here.…”
Section: Geologfc and Hydrologic Settingmentioning
confidence: 99%
“…If surface-water runoff at the site were making a significant contribution to the total mine outflow, it would be expected that the TDS would be considerably less than that observed. Water from the stream at Chesnut Branch and water entering the infiltration basin have TDS concentrations that are generally less than 500 mg/L (Dinger et al 1990). …”
Section: Hydrogeochemistrymentioning
confidence: 99%